Trends and prognostic rowing speeds - Kleshnev, V. (BioRow, 2019)
To begin, we will make a small note about terminology. It is very often the case that rowers and coaches focus too much on boat movement and so very often, talk about: "boat speed", "how can we make the boat to go faster?", etc. In actual fact, the rower`s mass is the biggest part of rower-boat system, and our biomechanical models use its movement as the main efficiency criterion, so it makes sense to shift the focus from the boat to the rower, or to `rowing` in general. Indeed, in other sports, nobody says "bicycle speed" or "ski/skate speed", or "how can I make my running shoe to go faster?". In these cyclic sports, the athlete sits on top of the equipment and interacts with the environment through it similarly to rowing, and people in these sports talk about "skier/skater speed" or simply "cycling/running speed". In fact, average speeds of the boat and rower over the stroke cycle are equal, so the "boat speed" is the same as the "rowers` speed". Therefore, here and onwards we will only discuss "rowing speed", unless we are specifically analysing instantaneous boat velocity, which is different from rower velocity inside the stroke cycle. .... Concluding, the random nature of the weather and lack of information about wind during World regattas make trends of rowing speed quite difficult to analyse. It is possible to say that within a small degree of probability, average rowing speed grows about 0.06% per year, which means the average race is about 2s faster every 10 years. Different trends were found in various events, and the fastest growth was found in W8+ (more than 4s over 10 years), which probably reflects tougher competition in this event based on wider participation of women in rowing and development of National squads in this event.